ANALISIS KONSENTRASI RASIO INDUSTRI BESAR DAN SEDANG DI INDONESIA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 -2017) - Miar Miar; Kiki Ronaldo Batubara (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2019)
This study examines the concentration ratio of large and medium industries in Indonesia (Empirical Study of Food and Beverage sub-sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2013-2017 Period). The purpose of this study to analyze how the concentration ratio of the food and beverage industry in Indonesia and find out how much the company is able to dominate the market. The data used in this study are secondary data obtained from the Indonesia Stock Exchange (IDX) and browsing the internet website as a support. The analytical method used in this study is the concentration ratio, hierfindahl index, and multiple linear regression analysis methods with the help of SPSS 21. The results of this study indicate that the market structure of the food and beverage industry in Indonesia for the period 2013-2017 using CR4 is a full oligopoly structure in which the 4 largest companies control about 88% market share, while CR8 is a monopoly structure in which the 8 biggest companies control about 97% market share. While the herfindahl index has an oligopoly structure. In this study shows that the variable capital has a positive and significant effect on the concentration ratio while the variable of labor and value added has a significant negative effect on the concentration ratio of large and medium industries in Indonesia. Variable labor capital and value added have a significant and significant effect on the concentration of large and medium industry ratios in Indonesia.